Study of Carbon Sequestration in Forest Ecosystems in DRC - Kabeya, Marie (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to investigate the study of carbon sequestration in forest ecosystems in DRC. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on carbon sequestration in DRC's forests underscores their crucial role as significant carbon sinks. These forests store substantial amounts of carbon in biomass and soils, contributing significantly to global climate regulation efforts. However, challenges like deforestation and illegal logging threaten this capacity, highlighting the importance of sustainable forest management and conservation. Enhancing carbon sequestration in DRC's forests is essential for mitigating climate change impacts and preserving biodiversity. Unique Contribution to Theory, Practice and Policy: Ecological succession theory, resource allocation theory & social-ecological systems theory may be used to anchor future studies on the study of carbon sequestration in forest ecosystems in DRC. Encourage the adoption of sustainable forestry practices that enhance carbon sequestration while supporting biodiversity conservation and local livelihoods. Align forest management policies with national and international climate change mitigation goals, emphasizing the role of forests as natural carbon sinks.